The copycat fish - Donovan, Gail, 1962-; Clar, David Austin (New York : Night Sky Books, 2001)
Rainbow Fish is angry that Tug copies everything he does, especially when their teacher, Miss Cuttle, picks them to work on a project together.
Keywords: Fishes -- Fiction; Imitation -- Fiction; Schools -- Fiction; Cooperation -- Fiction